Optimizing teachers' autonomy to use information and communications technology in Indonesian classrooms - Sekar Jasmine Noegroho; Natasya Zahra (Center for Indonesian Policy Studies (CIPS), 2024)
Efforts to digitize Indonesia's education sector are ongoing, however the unprecedented Covid-19 pandemic escalated the need for reform (UNICEF, 2021). Due to school closures and the enactment of socia distancing measures, teachers and students had to adjust to online learning and adopt information and communications technology (ICT) tools in order to continue their studies. Such a rapid transition forced teachers to experiment with new ways of engaging students by leveraging various digital platforms including video conferencing tools, and other online resources (Mahdum et al., 2019). Due to the circumstances, the Ministry of Education, Culture, Research and Technology (MOECRT), granted schools the autonomy to utilize any ICT tools that best met their needs through the Distance Learning Guide (Rasmitadila et al., 2020; Ministry of Education and Culture [MOEC], 2020a). Going forward, these changes to policy are further supported by the Merdeka Belajar initiative.
Keywords: 330